2015
DOI: 10.1007/s10461-015-1192-x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Personalized Text Message Reminders to Promote Medication Adherence Among HIV-Positive Adolescents and Young Adults

Abstract: HIV-positive adolescents and young adults often experience suboptimal medication adherence, yet few interventions to improve adherence in this group have shown evidence of efficacy. We conducted a randomized trial of a two-way, personalized daily text messaging intervention to improve adherence to antiretroviral therapy (ART) among N=105 poorly adherent HIV-positive adolescents and young adults, ages 16–29. Adherence to ART was assessed via self-reported visual analogue scale (VAS; 0–100%) at 3 and 6-months fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
218
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(224 citation statements)
references
References 40 publications
(42 reference statements)
4
218
0
2
Order By: Relevance
“…11 A recent US study among adolescents and young adults found that self-reported ART adherence was higher among those who received personalized daily text message messages. 12 Further, a systematic review found that text message reminders can help improve adherence in other chronic diseases such as diabetes, or infectious diseases such as tuberculosis. 27 text message messaging have been shown to improve attendance at appointments and behaviour change outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…11 A recent US study among adolescents and young adults found that self-reported ART adherence was higher among those who received personalized daily text message messages. 12 Further, a systematic review found that text message reminders can help improve adherence in other chronic diseases such as diabetes, or infectious diseases such as tuberculosis. 27 text message messaging have been shown to improve attendance at appointments and behaviour change outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Half (k = 7) of these efficacious, theory-based eHealth interventions were US-based [32] [33] [24, 30, 31, 34, 35]. Most (k = 11) of these efficacious, theory-based interventions implemented eHealth using electronic devices that were more technologically advanced (e.g., multimedia messaging) instead of or in conjunction with SMS texting.…”
Section: Resultsmentioning
confidence: 99%
“…[16] [17] Garofalo and colleagues recent work in this area with 105 adolescents and young adults where two-way daily SMS texts were provided to non-adherent youth demonstrated a significant improvement in self-reported adherence and high satisfaction scores. [18] Furthermore, a pilot study using personalized, interactive, daily SMS text messages demonstrated significant improvement among 14-to-29 year olds living with HIV with poor self-reported adherence rates. [19] Phone Based Outreach.…”
Section: Outreach Between Clinic Visitsmentioning
confidence: 99%
“…[20] [21] In a recent review, harnessing mobile phone technology was identified as a promising area for future interventions encouraging optimal adherence among YLWH. [18] Furthermore, evidence suggests using phone-based technology to engage adolescent social support networks may promote optimal engagement in care and adherence to medications. [22,23] A recent study of a phone-based support intervention among nonadherent YLWH found that it was acceptable and feasible among youth and clinic staff.…”
Section: Outreach Between Clinic Visitsmentioning
confidence: 99%